2009
DOI: 10.1016/j.eurpsy.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

An increase in substance misuse rather than other mental disorders has led to increased forensic treatment rates in the Czech Republic

Abstract: It is suggested that limited access to appropriate care forces psychiatric patients towards forensic treatment or to the prison system. According to our data, the number of prisoners, the number of hospitalized psychiatric patients (from 1987 to 2007), the number of court ordered forensic treatments in the Czech Republic (from 1991 to 2007), and the rate of people in psychiatric and sex offender forensic treatment has remained constant. However, an increase (162%) in number of treatments imposed for abusing il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This does not necessarily show in the ten-year intervals that we chose for the presentation of the data (e.g. Czech Republic): after the steep drop in the post-revolutionary years, the prison population had gradually increased to the level of before 1989 again, raising the question as to whether people with mental health problems, especially with drug addiction [34], may have replaced dissidents in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…This does not necessarily show in the ten-year intervals that we chose for the presentation of the data (e.g. Czech Republic): after the steep drop in the post-revolutionary years, the prison population had gradually increased to the level of before 1989 again, raising the question as to whether people with mental health problems, especially with drug addiction [34], may have replaced dissidents in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…FT can be imposed either in the inpatient or outpatient setting and can be ordered separately, in addition to punishment or instead of a punishment. Although no legal standard specifies them, FT is traditionally ordered in four areas: a) psychiatry b) sex offender treatment (that is, in offenders with paraphilias and other sexual disorders) c) substance abuse (Vevera et al, 2009) and d) pathological gambling. These treatments can also be imposed in combinations, e.g.…”
Section: Forensic Treatment Sentencingmentioning
confidence: 99%
“…Data from the registry of the Ministry of Justice does not show a significant rise of FT sentences in the past decade; the numbers of ordered (both outpatient and inpatient FT) oscillate around 600 treatments a year (Figure 1). Since 1990 there has been a rise in ordered FT-476 cases in 1991 to 592 in 2007; this rise is probably due to increased substance abuse treatment (Vevera et al, 2009). There has been only one prevalence study regarding ordered PT diagnosis; this showed on the sample of PH Bohnice (catchment area 1.2million) between the 2002-2007 a rise of PT patients with substance abuse with reduction of PT ordered for schizophrenia (Vevera et al, 2009).…”
Section: Inpatient Ftmentioning
confidence: 99%
See 1 more Smart Citation